Canid herpesvirus 1 Preferentially Infects Polarized Madin-Darby Canine Kidney Cells from the Basolateral Surface - Mohamed Eisa; Samar Micky; Angela Pearson (Viruses, 2022)
Canid herpesvirus 1 (CHV-1) infects polarized canine epithelia. Herein, we present our initial work characterizing CHV-1 infection of Madin-Darby canine kidney (MDCK) cells that were polarized on trans-wells. We previously showed that infection of these cells in non-polarized cultures stimulated the formation of extensive lamellipodial membrane protrusions. Uninfected polarized MDCK cells already form extensive lamellipodial membrane protrusions on the apical surface in the absence of virus. Using scanning electron microscopy, we found that CHV-1 infection does not lead to a change in the form of the lamellipodial membrane protrusions on the apical surface of polarized MDCK cells. We found that CHV-1 was able to infect polarized cultures from either the apical or basolateral side; however, higher viral titers were produced upon infection of the basolateral side. Regardless of the side infected, titers of virus were higher in the apical compartment compared to the basal compartment; however, these differences were not statistically significant. In addition to cell-free virus that was recovered in the media, the highest amount of virus produced remained cell-associated over the course of the experiment. The efficiency of CHV-1 infection of the basolateral side of polarized epithelial cells is consistent with the pathobiology of this varicellovirus.